Avaliação da qualidade da imagem e dose na paciente em mamografia analógica e digital - Santos, Amanda Cristina dos (2011)
This work has been motivated by a larger study, proposed by the International Atomic Energy Agency (IAEA). The aim of this work was to estimate the incident kerma (Ki) and mean glandular dose (Dg) in patients who underwent mammograms in craniocaudal projections (CC) and mediolateral-ablique (MLO), at analog and digital systems. The estimation was performed using mathematical calculations based on computational studies using Monte Carlo simulations. This study was part of a larger study in mammography, coordinated by the IAEA, whose data were included in the representation of Brazilian data in the study of Latin America. Mammograms with 50% of glandular tissue and 50% of fat were selected. Data from the radiographic technique used in the examinations, as well as the compressed breast thickness were recorded in spreadsheets and specific calculation was made based on output tests of the X-ray tube for mammography. In addition, the mammograms were analysed with the criteria of image quality. The amount of examinations was 100 mammograms, 50 analog and 50 digital. The results showed that the images were largely accepted as the criteria for image quality established by the IAEA, with better results from digital system. The values of Ki and Dg for the phantom were according to the recommended, but those calculate for the patients were higher, especially the Ki. Digital system produced lower dosis and better results on image quality. The results suggests that the examinations must be conducted with due care in order to offer image quality in dosis as low as reasonably achievable. The permanent training of mammographers should be conducted in a manner to provide exams with quality, protecting the patient and maintaining the quality of service to all patients treated.